2017
DOI: 10.1039/c6dt04513h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophenoxylation of internal alkynes catalysed with a heterobimetallic Cu-NHC/Au-NHC system

Abstract: A straightforward method for the hydrophenoxylation of internal alkynes, using N-heterocyclic carbene-based copper(i) and gold(i) complexes, is described. The heterobimetallic catalytic system proceeds via dual activation of the substrates to afford the desired vinylether derivatives. This methodology is shown to be highly efficient and tolerates a wide range of substituted phenols and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…[2,11] Theoriginal structural characterization of these dicopper hydride complexes,along with related silver analogues,h as been pioneered by Sadighi and co-workers ( Figure 1). [14] One approach to prepare complexes containing MÀHÀM' linkages is through the addition of am onomeric metal hydride complex to as uitable electrophilic fragment. [14] One approach to prepare complexes containing MÀHÀM' linkages is through the addition of am onomeric metal hydride complex to as uitable electrophilic fragment.…”
mentioning
confidence: 99%
“…[2,11] Theoriginal structural characterization of these dicopper hydride complexes,along with related silver analogues,h as been pioneered by Sadighi and co-workers ( Figure 1). [14] One approach to prepare complexes containing MÀHÀM' linkages is through the addition of am onomeric metal hydride complex to as uitable electrophilic fragment. [14] One approach to prepare complexes containing MÀHÀM' linkages is through the addition of am onomeric metal hydride complex to as uitable electrophilic fragment.…”
mentioning
confidence: 99%
“…Moreover, predictive catalytic results by DFT calculations proposed a new generation of digold complexes [94], where both metal moieties are linked by an alkylic bridge. Recently, Cazin et al have reported the hydrophenoxylation of diphenylacetylene catalyzed by a combined Cu(NHC)/Au(NHC) catalytic system [95]. Nevertheless, they performed experimental studies to determine the solvent and temperature effect in the hydrophenoxylation reaction and they found a higher conversion to the desired product under solvent-free conditions.…”
Section: Dual-assisted Hydroalkoxylation Processmentioning
confidence: 99%
“…Despite detailed studies on the preparation and reactivity of symmetric dinuclear coinage metal hydrides, little is known about heterobimetallic compounds with asymmetric M−H−M′ moieties. Combinations of copper and gold NHC complexes catalyze the addition of phenols to internal alkynes with activities that are greater than the individual components of the mixture …”
Section: Figurementioning
confidence: 99%